Thermodynamics and Chemistry - DeVoe, Howard; Open Textbook Library (Open Textbook Library, 2019)
Thermodynamics and Chemistry is designed primarily as a textbook for a one-semester course in classical chemical thermodynamics at the graduate or undergraduate level. It can also serve as a supplementary text and thermodynamics reference source.
1 Introduction -- 2 Systems and Their Properties -- 3 The First Law -- 4 The Second Law -- 5 Thermodynamic Potentials -- 6 The Third Law and Cryogenics -- 7 Pure Substances in Single Phases -- 8 Phase Transitions and Equilibria of Pure Substances -- 9 Mixtures -- 10 Electrolyte Solutions -- 11 Reactions and Other Chemical Processes -- 12 Equilibrium Conditions in Multicomponent Systems -- 13 The Phase Rule and Phase Diagrams -- 14 Galvanic Cells
In English.
Description based on online resource
Keywords: Chemistry -- Textbooks